If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2f = 8f + -54 Reorder the terms: 2f = -54 + 8f Solving 2f = -54 + 8f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-8f' to each side of the equation. 2f + -8f = -54 + 8f + -8f Combine like terms: 2f + -8f = -6f -6f = -54 + 8f + -8f Combine like terms: 8f + -8f = 0 -6f = -54 + 0 -6f = -54 Divide each side by '-6'. f = 9 Simplifying f = 9
| z^2+15z+24=-32 | | 12x-(6x-4)=58 | | 6-2x^2=9x+15 | | 3x^2+6x=10 | | 18y-27=10y-25 | | 2x(2-x)=x(2-x)+35 | | 3b+b-10=0 | | 5(2q+6)=25 | | 33=[3x+8]3x | | 6(x-1)=-3(2-x)+3x | | x^2-16x+7=0 | | 4p+6=26 | | 18-12y-2y=1 | | 4x-y=5 | | 59-7x=2x+20 | | 5x+12=-100-9x | | 5x+12=-100-9 | | p-(p+1)=6p(p-2)+5p | | -3-6x=13-8x | | 9x+5y=22 | | 6x+10=118-6x | | 1+4x=13+x | | 3(x-14)=24 | | -5+3x-2x=11-4 | | 12x+9=9x+24 | | 7x+8=5x-4 | | 2x^2+3x+10=0 | | 2x^2-3x-10=0 | | 3x^3+4x^2-15x=0 | | 6(-6+4)=6-11 | | 3z-iz=7-5i | | 6(5a+4)=-5a-11 |